Chinese classics The Scholars - Wu Jingzi (Chinese classics stories, 2017)
The Scholars,authored by Wu Jingzi , creates a capacious and vivid portrayal of the community life of the feudal society and mirrors various filthy phenomena rampant during the last stage of feudalism. The book offers a vivid portrayal of the various abnormal personages in the vanity fair of position and wealth and delineates the ugly performances of the scholars. Meanwhile, it embodies the writer's social ideal of revitalizing ancient rites and music, rejuvenating the ways of the world and public morality and saving the nation from peril. It is recognized as one of the great masterpieces of Chinese satirical fiction. This book is edited and translated by the famous translator Wang Guozhen, to introduce The Scholars to the foreign readers.